Bussines Model Canvas Pada Cafe Tampa Bakudapa Di Kabupaten Bolaang Mongondow - Yambo, Nesha Salshadilah; Memah, Melsje Yellie; Loho, Agnes Estephina (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2025)
Cafe Tampa Bakudapa, a pioneer of locally-themed cafes in Bolaang Mongondow Regency, utilizes the Business Model Canvas (BMC) to develop its business strategy. Research using accidental sampling on business owners shows that customers are predominantly women aged 17–40, both locals and tourists. The key values offered include comfort, local menus, complete facilities, and reservation services. Marketing is conducted through social media and word-of-mouth promotions, with customer relationships built through personalized service, discounts, and bonuses. Revenue comes from menu sales and event reservations, with key resources such as strategic location, trained staff, and technology. Main activities include food preparation, service, promotion, and entertainment, as well as partnerships with local suppliers and promoters. Costs consist of fixed and variable expenses. The café has implemented the nine BMC elements in an integrated manner, supporting its sustainability and competitiveness in the culinary industry.